2021
DOI: 10.18371/fcaptp.v4i31.190958
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude and Nature of the Shadow Economy in Ukrainian Border Regions

Abstract: The peculiarities of the formation and functioning of the shadow sector of economy of the border regions of Ukraine have been considered. It has been substantiated the importance of studying the nature of the emergence of the shadow economy and finding the effective tools for leveling the preconditions for its development.The main regularities and indicators of the emergence and growth of the shadow economy have been outlined. Among them there are the levels of tax burden and social protection, regulatory meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Previous findings concerning the main determinants of the shadow economy in regions are reviewed in Table 1. As it can be seen in Table 1, the determinants of the shadow economy may vary from region to region, although some general tendencies can be envisaged: many authors highlight the significance of taxation (Bilonizhko, 2006;Tafenau et al, 2010;Buehn, 2012;Polovyan, 2015;Gonzalez-Fernandez & Gonzalez-Velasco, 2015;Gasiūnas, 2018;Remeikiene et al, 2018;Davydova et al, 2020), standard of living (Kireenko et al, 2017;Remeikiene et al, 2018), labour market (Bilonizhko, 2006;Tafenau et al, 2010;Buehn, 2012;Vorobyev, 2015;Buček, 2017;Prytula et al, 2019), institutional factors (Polovyan, 2015) and corruption (Vorobyev, 2015;Borlea et al, 2017;Gillanders & Parviainen, 2018). Nevertheless, the results of some studies are contradictory, for instance, Buček's (2017) study found no evidence to prove the importance of particular types of taxes (e.g.…”
Section: Regional Shadow Economy and Its Determinants: Theoretical Backgroundmentioning
confidence: 99%
“…Previous findings concerning the main determinants of the shadow economy in regions are reviewed in Table 1. As it can be seen in Table 1, the determinants of the shadow economy may vary from region to region, although some general tendencies can be envisaged: many authors highlight the significance of taxation (Bilonizhko, 2006;Tafenau et al, 2010;Buehn, 2012;Polovyan, 2015;Gonzalez-Fernandez & Gonzalez-Velasco, 2015;Gasiūnas, 2018;Remeikiene et al, 2018;Davydova et al, 2020), standard of living (Kireenko et al, 2017;Remeikiene et al, 2018), labour market (Bilonizhko, 2006;Tafenau et al, 2010;Buehn, 2012;Vorobyev, 2015;Buček, 2017;Prytula et al, 2019), institutional factors (Polovyan, 2015) and corruption (Vorobyev, 2015;Borlea et al, 2017;Gillanders & Parviainen, 2018). Nevertheless, the results of some studies are contradictory, for instance, Buček's (2017) study found no evidence to prove the importance of particular types of taxes (e.g.…”
Section: Regional Shadow Economy and Its Determinants: Theoretical Backgroundmentioning
confidence: 99%